Pulmonary lymphangiomatosis: insights into an ultra-rare disease - Polke, Markus; Polke, N.; Piel, Stella; Brunnemer, Eva; Wälscher, J.; Buschulte, Katharina; Warth, Arne; Heußel, Claus Peter; Eichinger, Monika; Frankenstein, Lutz; Eichhorn, Martin E.; Miliauskas, S.; et al. (Respiratory research, 2024)
Pulmonary lymphangiomatosis (PL) is an ultrarare disease characterized by diffuse infiltration of the lung, pleura and/or mediastinum by abnormal lymphatic proliferation. Consented diagnostic or treatment approaches are not established. We therefore aimed to collect data on diagnostics and treatments in a cohort of patients with PL from a tertiary center for rare lung diseases.